Antitumor activity of bengamide ii in a panel of human and murine tumor cell lines: In vitro and in vivo determination of effectiveness against lung cancer - Ortigosa-Palomo, Alba; Porras Alcalá, Cristina; Quiñonero, Francisco; Moya-Utrera, Federico; Ortiz, Raúl; López-Romero, Juan Manuel; Melguizo, Consolación; Sarabia-García, Francisco Ramón; Prados, José (Elsevier, 2023)
Lung cancer is the most commonly diagnosed cancer and the one that causes the most deaths worldwide, so there is a need for therapies that improve survival rates. Products derived from marine organisms are a source of novel and potent antitumor compounds, but they present the great obstacle of their obtaining from the natural environment and the problems associated with the synthesis and biological effects of chemical analogues. In this work, a Bengamide analogue (Bengamide II) was chemically synthesized and in vitro and in vivo studies were performed to determine its antitumor activity and mechanisms of action. It was shown to have potent antiproliferative activity in lung cancer lines in 2D and 3D models. In addition, Bengamide II-treated cells showed G2/M and G0/G1 cell cycle arrest, together with a decrease in the proliferation marker Ki67. As for the mechanism of action, the treatment was associated with increased LC3-II expression and production of acidic vesicles signaling autophagy. In addition, Bengamide II treatment was associated with caspase-3 activation and DNA fragmentation related to apoptosis. Furthermore, a reduction of VEGFA expression, related to angiogenesis, was also observed. In vivo studies showed that Bengamide II markedly reduced tumor volume and metastases increasing survival. Additionally, it revealed no systemic toxicity in in vivo models at the therapeutic doses used, which is essential for its future clinical use. Taken together, the chemically synthesized bengamide analogue Bengamide II, is a promising drug for lung cancer treatment showing relevant antitumor activity and significant safety.
Keywords: Pulmones - Cáncer; Antineoplásicos; Organic synthesis; Bengamide II; Lung cancer; Antitumor; In vitro; In vivo